Predictive utility of inotropic scores in pediatric septic shock: A prospective observational cross-sectional study from a tertiary PICU in India. - Kumar , Santhosh; Nair, Shreya; Anitha C (Student's Journal of Health Research Africa, 2025)
Background Septic shock remains a leading cause of morbidity and mortality in children, particularly in resource-limited settings. Early recognition of high-risk patients is essential to improve outcomes. The Inotropic Score (IS) and Vasoactive-Inotropic Score (VIS) quantify cardiovascular support and reflect illness severity. This study aimed to evaluate the usefulness of the Wernovsky Inotropic Score (WIS) and VIS in predicting mortality among children with septic shock admitted to a tertiary care PICU. Objectives: To assess the predictive accuracy of the Wernovsky Inotropic Score (WIS) and Vasoactive-Inotropic Score (VIS) for in-hospital mortality in pediatric septic shock. Methodology This prospective, longitudinal study was conducted over 18 months (September 2022–March 2024) in the PICU of a tertiary care teaching hospital. Children aged 1 month to 18 years admitted with septic shock requiring vasoactive therapy were included. Patients who had received inotropes for more than 6 hours before admission or had ≥2 organ dysfunctions were excluded. The Inotropic Score (IS) was calculated as [IS = Dobutamine + Dopamine + 100 × Epinephrine (μg/kg/min)] at 24 and 48 hours. Data were analysed using appropriate statistical tests, and ROC curves were plotted to determine predictive accuracy. Results Among 21 patients, 13 (61.9%) died. Mean VIS and WIS were significantly higher in nonsurvivors (VIS: 53.55 ± 16.71 vs 29.04 ± 13.11, p = 0.002; WIS: 39.80 ± 14.78 vs 20.72 ± 12.57, p = 0.006). ROC analysis showed strong predictive performance (VIS AUC = 0.837; WIS AUC = 0.865). Conclusion Both WIS and VIS are reliable predictors of mortality in pediatric septic shock. VIS demonstrated higher sensitivity, while WIS showed better specificity, aiding early prognostication and management of critically ill children. Recommendations WIS and VIS can be used to help predict mortality among children with septic shock.